Optimisation of Planting Densities and Nitrogen Requirement for Bt Cotton under High Density Planting System - Kavya, D.; Kumari, Ch. Pragathi; Sreenivas, G.; Prakash, T. Ram; Triveni, S. (International Journal of Bio-resource and Stress Management, 2023)
A field investigation was conducted at College farm, Professor Jayashankar Telangana State Agriculture University, Rajendranagar, Hyderabad, Telangana, India during kharif (July to January, 2021–22)to optimise the planting density and nitrogen dose on cotton yield and economics. The experiment was laid out in factorial RBD consisting of four levels of planting densities viz. 90×15 cm2, 90×20 cm2, 90×30 cm2 and 90×60 cm2 as factor I treatments and 4levels of nitrogenviz., 90, 120, 150,180 kg N ha-1 as factor II treatments and replicated thrice. The results revealed that with higher planting density ofspacing 90×15 cm2 (74,074 plants ha-1) reported significantly higher seed cotton yield (2176 kg ha-1), Gross returns (` 1,31,114 ha-1) and net returns (` 70,150 ha-1) and was at par with spacing 90×20 cm2 (55,555 plants ha-1) over other planting density of spacing 90×30 cm2 (37,037 plants ha-1) and 90×60 cm2 (18,518 plants ha-1). Lower plant density of spacing 90×60 cm2 significantly performed better with respect to yield attributes viz, number of picked bolls plant-1 (18.2), boll weight (5.1 g) and seed cotton yield (95.0 g plant-1). Among the nitrogen doses, 150 kg N ha-1 recorded significantly higher seed cotton yield (2072 kg ha-1), Gross returns (`Rs. 1,24,818), Net returns (`Rs. 69,407) and B:C (2.25) over other nitrogen doses tested. However, the interaction effects did not differ significantly for all the parameters studied.